1990
DOI: 10.1038/eye.1990.83
|View full text |Cite
|
Sign up to set email alerts
|

Precorneal residence times of sodium hyaluronate solutions studied by quantitative gamma scintigraphy

Abstract: SummarySodium hyaluronate solutions have been advocated in the management of a variety of dry-eye states. By virtue of their non-Newtonian rheological properties, for mulations exhibiting high zero-shear viscosities may be used as an artificial tear with the expectation of prolonged precorneal residence times and improved tolerance.Quantitative gamma scintigraphy was used to evaluate the residence times of 0.2% and 0.3% sodium hyaluronate solutions and a polymer-free solution of buffered saline in 12 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
2
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 21 publications
3
51
2
2
Order By: Relevance
“…29 Moreover, viscoelastic properties and long ocular surface residence time of SH have rendered it effectively increase tear film stability and corneal wettability, and reduce the tear evaporation rate. 30 It was recently reported that a hyaluronate receptor, CD44, is expressed in human and rabbit corneas. 31,32 SH promoted human cornea epithelial cell migration by the adhesion between CD44 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, viscoelastic properties and long ocular surface residence time of SH have rendered it effectively increase tear film stability and corneal wettability, and reduce the tear evaporation rate. 30 It was recently reported that a hyaluronate receptor, CD44, is expressed in human and rabbit corneas. 31,32 SH promoted human cornea epithelial cell migration by the adhesion between CD44 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand S3, which resulted in the longest TBUT values, contains hyaluronic acid, which has been reported as a high-viscosity agent equivalent to mucus glycoprotein, with the ability to adhere to epithelial cells [19]. Previous research on surface residence time found that solutions containing sodium hyaluronate had a mean half-life on the ocular surface of 321 s, significantly longer than others with hydroxypropyl methyl cellulose, which is a viscosity agent for S4, or a buffered saline solution such as S1 and S2 [20,21]. Other reports disclosed that tear substitutes with sodium hyaluronate provide better tear film stability, as determined by NIBUT values, than those with hydroxypropyl methyl cellulose [22], and resulted in better patient reported comfort [23].…”
Section: Discussionmentioning
confidence: 98%
“…Increasing the rate of evaporation of the tear film would reduce the time to equilibrium for the volume. For this reason, the time for removal of the drug from the system is also over predicted, with experimental results taking 900-1000 s for a tracer compound in a 25 μL drop to reach 1% of its original value [48,49] while the model predicts this time to be 1454 s. Again, increasing the rate of evaporation would result in the model predicting a lower value. When the rate of evaporation was set at 4 times the value originally used in the model, the time for removal of the drug decreased by ~9% [40].…”
Section: Accepted Manuscriptmentioning
confidence: 92%